(untitled) (Revista Internacional de Folkcomunicação, 2018)
ABSTRACT This work is a study on the feast of Santo Antônio in the quilombola community of the Mandira in Cananéia - SP. The research aims to analyze the Feast of Santo Antônio as process of communication to the formation of the social imaginary and the quilombola identity. The methodology used includes bibliographical, documentary and ethnographic research, with the following techniques: participant observation and interviews with members of the Mandolan quilombola community. This research bring as result that the quilombola, as a declassed population, develops means of communication through folk-communicative expressions from their religious practices, such as the Feast of Santo Antônio, allowing it collectivelly express their feelings and to find protection from social injustices that it suffer constantly. KEY-WORDS Communication; Citizenship; Social imaginary; Quilombola; Popular religiousness.